The energy resources of the Eastern Mediterranean. The role of Turkey - Μπαλοδήμος, Στέργιος (Πανεπιστήμιο Πελοποννήσου, 2016)
This thesis through its pages will firstly outline the energy profile of both the Eastern Mediterranean countries and the region, and secondly, the key role of Turkey in the outcome of the issues raised at the bilateral level with neighboring countries. In the energy equation of the eastern Mediterranean, Turkey is perhaps the most important variable in this sensitive chord as bilateral relations with countries - actors in the region have tried quite a few / several times before. The situation so far shows the strong interest of Turkey for participation and pooling of reserves. The practical economic gain (and not only) this process remains to be seen from the negotiations that followed between both countries and international organizations.
Keywords: Φυσικοί πόροι; Ενεργειακή πολιτική; Ενεργειακοί πόροι; Μεσόγειος, Περιοχή της; Ανατολική Μεσόγειος; Ενεργειακοί πόροι; Τουρκία; Ελλάδα; Κύπρος